The role of microbiota in autism spectrum disorder: A bibliometric analysis based on original articles - Lin, Xiaoling; Zhou, Runjin; Liang, Dandan; Xia, Lingling; Zeng, Liying; Chen, Xiaogang (Frontiers in Psychiatry, 2022)
Background: Gastrointestinal (GI) symptoms can be observed in Autism Spectrum Disorder (ASD) children. It is suggested that gut microbiota and its metabolites are not only associated with GI symptoms, but also with behaviors of ASD. The aim of this study is to explore the development context, research hotspots and frontiers of gut microbiota and ASD from 1st January, 1980- 1st April, 2022 by bibliometric analysis. Methods: Publications of ASD and gut microbiota research from 1st January, 1980- 1st April, 2022 were retrieve from the Web of Science Core Collection (WoSCC). Publications and citations trends were analyzed by Excel 2010. CiteSpace was used to analyze countries/regions, authors, institutes, references, keywords, and visualize the knowledge map. Results: A total of 1027 literatures were retrieved, and 266 were included after screening. The most published country and institute are the United States (85) and King Saud Univ (18). AFAF ELANSARY (16) published the most articles while FINEGOLD SM (139) owned the highest co-citations. Hotspots and emerging trends in this area may be indicated by co-cited references and keywords and their clusters, including “gut-brain axis”, “behavior”, “chain fatty acid”, “brain”, “fece”, “propionic acid”, “clostridium perfringens”, and “species clostridium innocuum”. Conclusion: The United States takes a dominant place in this field. Research focuses on the alterations of gut microbiota composition and its metabolites, among which the roles of the genus of Clostridium and metabolites of short chain fatty acids especially propionic acid are priorities. Fecal microbiota transplantation (FMT) is a promising complementary therapy. In general, research in this area is sparse, it still has great research prospect.